LEGAL CERTAINTY IN THE TRANSFER OF LAND RIGHTS THROUGH AUCTION: A CASE ANALYSIS OF THE SUPREME COURT DECISION NO. 920 K/PDT/2020 ON THE CANCELLATION OF EXECUTION SEIZURE OF ENCUMBERED LAND - Farly Kanserano Jabiy; Hanafi Tanawijaya (RADJA PUBLIKA, 2025)
This article examines the legal certainty of transferring land rights through public auction in Indonesia, with a specific focus on the Supreme Court Decision No. 920 K/Pdt/2020. The decision addresses a case involving a request to annul the execution seizure of encumbered land obtained through auction. The study applies a normative juridical method and uses statutory and case approaches to explore the alignment of legal proceedings with positive law. It particularly investigates the auction process, the nature of mortgage rights (Hak Tanggungan), and the legal implications for third parties claiming inheritance rights. The decision ultimately reaffirmed the purchaser's rights and provided a precedent supporting legal certainty in auction-based land transfer. This analysis highlights the importance of executing court decisions with enforceable power and the role of mortgage law in ensuring creditor protection and legal clarity for auction buyers.